Field Evaluation of a Transplanter and a Collector Under Development for Korean Spring Cabbage Production in Greenhouses - Md Nasim Reza; Md Rejaul Karim; Md Razob Ali; Kyu-Ho Lee; Emmanuel Bicamumakuba; Ka Young Lee; Sun-Ok Chung (AgriEngineering)
Cabbage (Brassica rapa L. ssp. Pekinensis) is an important vegetable crop in the Republic of Korea, due to its essential role in kimchi production. However, labor shortages and an aging population necessitate mechanization to sustain productivity. This study aimed to evaluate the field performance of a cabbage transplanter under development with a commercial transplanter and a cabbage collector under greenhouse conditions. This study evaluated transplanting efficiency, planting performance, and yield of cabbage using seedlings at three distinct age groups (30, 35, and 43 days). A cabbage transplanter (Transplanter A) under development, a commercial model (Transplanter B), and manual transplanting were used for comparative analysis. At harvest, a tractor-mounted cabbage collector was used to collect and pack all the cabbages. Transplanter A demonstrated a forward speed of 1.27 km/h and an average planting rate of 2365 seedlings/h, significantly higher than manual transplanting (513 seedlings/h). The effective field capacity (EFC) ranged from 0.11 to 0.13 ha/h, compared to 0.019–0.028 ha/h for manual planting. While Transplanter A showed a higher missing transplant rate (18.17%) than Transplanter B (7.67%), it maintained consistently lower bad planting rates (2.5–4.5%) compared to Transplanter B (3.3–8.8%). In addition, it produced significantly higher cabbage weights (6070 g/plant) and better root metrics than manual transplanting. The cabbage collector achieved 100% efficiency with no crop damage or contamination. The transplanter under development proved effective for greenhouse use, offering faster operation, better planting accuracy, and higher yields, supporting broader mechanization in Korean agriculture.